Youri Norstein - Le meilleur des court métrages d'animations - Norstejn, Jurij Borisovic; Tjurin, Arkadij; Ivanov-Vano, Ivan Petrovic (Animatikc - Les maîtres de l'animation russe)
Yuri Norstein is universally considered the most remarkable director to emerge from the current generation of Russian animators. Although his body of completed work is less than 80 minutes in length, its impact has been so profound that he is regularly ranked one of the world's greatest contemporary directors. Most of his films were made by the same small team - his wife the artist Francesca Yarbusova, his cameraman the late Alexander Zhukovsky, and the late composer M. Meyerovich. All of the films included in this edition of the Norstein Collection were digitally re-mastered from new 35mm prints under the supervision of Zhukovsky, to whom it is dedicated. [www.chaletfilms.com]